2018
DOI: 10.1002/ecs2.2344
|View full text |Cite
|
Sign up to set email alerts
|

Fire and plant invasion, but not rodents, alter ant community abundance and diversity in a semi‐arid desert

Abstract: Human activities are increasing the size, frequency, and severity of disturbance across earth's ecosystems including deserts. Ants are important drivers of ecosystem function and are good bioindicators of ecosystem sensitivity to disturbance and change. Rodents also play an important role in ecosystem response to disturbance and often compete with ants for resources. The purpose of our study was to test the main and interactive effects of fire, rodent activity, and time on ant forager abundance, species richne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 57 publications
1
7
1
Order By: Relevance
“…Ostoja et al (2009) reported lower ant diversity in cheatgrass-dominated plots compared with sagebrush intact plots in the Great Basin which is a typical vegetation conversion after fire as seen in our plots. These results are consistent with our previous research at the Great Basin site, where ant species diversity was reduced in burned areas but ant abundance was unaffected (Day, Bishop, & St. Clair, 2018). In that study, abundance of most species was reduced in burned plots, but the abundances of some dominant ant species increased, which kept overall ant abundance in burned areas similar to those in unburned areas.…”
Section: Invertebrate Responses To Firesupporting
confidence: 92%
See 2 more Smart Citations
“…Ostoja et al (2009) reported lower ant diversity in cheatgrass-dominated plots compared with sagebrush intact plots in the Great Basin which is a typical vegetation conversion after fire as seen in our plots. These results are consistent with our previous research at the Great Basin site, where ant species diversity was reduced in burned areas but ant abundance was unaffected (Day, Bishop, & St. Clair, 2018). In that study, abundance of most species was reduced in burned plots, but the abundances of some dominant ant species increased, which kept overall ant abundance in burned areas similar to those in unburned areas.…”
Section: Invertebrate Responses To Firesupporting
confidence: 92%
“…In our study, fire had very little effect on ant abundance; however, fire reduced ant species diversity at both sites (Tables 5 and 6; Figures 1 and 2). Ostoja et al abundance was unaffected (Day, Bishop, & St. Clair, 2018). In that study, abundance of most species was reduced in burned plots, but the abundances of some dominant ant species increased, which kept overall ant abundance in burned areas similar to those in unburned areas.…”
Section: Invertebrate Responses To Firementioning
confidence: 62%
See 1 more Smart Citation
“…Ants have been shown to limit the dispersion and burrowing activities of rodents (Panteleeva et al 2016), and both species can limit each other's access to seeds through exploitative competition (Brown et al 1979;Valone et al 1994). However, the idea that rodents and ants vigorously compete for seed resources has been disputed; rodents prefer larger seeds, while ants prefer smaller seeds (Connolly et al 2014;Day et al 2018;Martyn et al 2022). Rodent activity can increase the abundance of smaller seed-producing species that ants tend to prefer (Brown et al 1979;Johnson 2001;Bishop et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, there was little evidence in the Great Basin Desert that rodent exclusion signi cantly affected ant abundance (Day et al 2018) (Reed et al 2004) due to altered habitat conditions (Holbrook et al 2016). Fire affects ant activity and the plant community processes they mediate (Day et al 2018). Ant response to re varies by species, with some increasing in abundance while others decrease (Ostoja et al 2009 The Great Basin Desert is a semi-arid ecosystem occupied by rodents and western harvester ants, where both taxa play critical ecological roles (Uhey and Hofstetter 2022).…”
Section: Introductionmentioning
confidence: 99%